(untitled) (Acta Entomologica Serbica, 2018)
Professor Dr Duška Simova-Tošić, retired full-professor of entomology at the Faculty of Agriculture, University of Belgrade, died on 19 June 2018. In 1956, she graduated from the Faculty of Natural Sciences and Mathematics, Department of Biology, in Skopje. After completing her studies, she worked for one year as a curator-entomologist at the Natural History Museum in Skopje, and from 1958 to 1962 as an assistant at the Faculty of Natural Sciences and Mathematics, University of Skopje. From 1962, she was employed as an assistant at the Faculty of Agriculture of the University of Belgrade, where, after moving up through all academic teaching levels, she worked as an entomologist until her retirement on October 1, 1999. At the same faculty, she obtained her MSc, and subsequently PhD. She defended her master’s thesis, “Contribution to knowledge of the harmful fauna of Cecidomyiidae of Serbia”, in 1964, and in 1969, she defended her doctoral dissertation entitled “Cecidomyiidae of Serbia and the importance of some morphological characters for its determination”. She was elected assistant professor in 1971, associate professor in 1977, and full professor in 1982. In 1968, she specialized in nematology at the Nematology Laboratory in Wageningen in the Netherlands, and on study tours in the USSR (1972) and the Netherlands (1973 and 1976). During her time at the Faculty of Agriculture in Belgrade she lectured on the subject of Special Entomology and Insect Ecology at the Department for the Protection of Plants and Food Products, and Entomology at the Department of Farming. During her postgraduate studies in entomology, she gave lectures in the fields of Insect Physiology, Insect Systems and Entomology. She also taught Entomology at the Faculties of Agriculture in Skopje and Novi Sad, and in high schools in Vršac and Zrenjanin. She had a reputation as a strict teacher, but one that was respected by her students. In 1999, she was awarded an honorary professorship of the University “Saints Cyril and Methodius” in Skopje. She mentored dozens of master’s theses and doctoral dissertations at the Faculties of Agriculture at the universities of Belgrade, Novi Sad, Skopje and Zagreb. Professor Duška Simova-Tošić was dedicated to the teaching of students, and, as author or co-author, she organized a number of teaching aids: “Insect Determination Charts” (1969), “Insect Collection Handbook” (1969), “Practicum of Special Entomology” (1975 and 1995), scripts and textbooks on General Entomology (1985, 1987) and Special Entomology (1985, 1987). For students of the Faculty of Environmental Sciences in Skopje she wrote the textbook “Environmental Entomology (Part I)”, Skopje (1987). Her field of scientific interest was the study of gall midges (Cecidomyiidae), crane flies (Tipulidae and Limoniidae), and other species and groups of insects. Her main preoccupations were Cecidomyiidae and Tipulidae, which she studied from the aspect of systematics, taxonomy, development cycle, natural enemies, harmfulness and importance in plant production. Her work of many years within these taxonomic groups, which continued after her retirement, resulted in published monographs: “Crane Flies − Tipulidae (Diptera-Insecta)” in “Fauna of Macedonia III” (1977); “Tipulidae” (Insecta, Diptera) in “Fauna of Durmitor” (1987); “Atlas of Gall Midges (Diptera: Cecidomyiidae: Cecidomyiinae)” (2014), and as a special edition of the journal Acta entomologica Serbica, “Phytophagous Species of Gall Midges in Serbia, Diptera: Cecidomyiidae, Cecidomyiinae” (2016). Also, in agricultural entomology, she was the author of the chapter “Soybean Pests and Diseases” in the monograph “Soya − Production and Processing” (1995), and one of the authors of the Handbook on Quarantine and Pest Control (1980, Belgrade). Depending on the subject of interest at a given time during her working life, Prof. Dr. Simova-Tošić took part in the realization of programs in several scientific research projects. She participated in scientific meetings and congresses at home and abroad. She developed strong scientific and professional cooperation with colleagues from all republics of ex-Yugoslavia and from abroad. However, her greatest scientific cooperation was with scientists studying Tipulidae and Cecidomyiidae from the former USSR, especially Ukraine, and from the Netherlands, Germany, England and Romania. Particular mention should be made of her close cooperation with the Czech entomologists Marcela Skuhravá and Václav Skuhravý, with whom she published a number of papers on the topic of Cecidomyiidae. The monograph “Cecidomyiidae Fauna in Europe and Asia 1955-2008” by Skuhravá and Skuhravý cites the results of Prof. Simova’s research on the number of established species of Cecidomyiidae, not only in Serbia, but also in all the republics of former Yugoslavia. Thanks to her dedicated work and exhaustive research, the fauna of Serbia’s gall midges is the best studied when compared to neighboring countries. Before retiring, Prof. Simova had established 283 species of gall midges in Serbia, but this was not the end of her activities and creative opus. After 2000, she published two monographs and eight scientific papers. According to the 2nd Annex to the knowledge of gall midges of Serbia published in 2008 in the journal “Bulletin of the Natural History Museum”, Belgrade, there are 19 species, 17 of which are new to Serbia, 5 to the fauna of gall midges of the Balkan Peninsula, and 4 are for the first time established for the former Yugoslav republics. With this data, and with another 24 species that have not been identified and for which it is reliably believed that they are new to science (as the author herself pointed out in her last paper), the total number of species that she identified during her life and work in Serbia was 326, among which there are invasive species, species that are new to the fauna of Serbia, new for the Balkan Peninsula and for Europe, and new to science. In addition to over a hundred scientific papers published in domestic and foreign journals and at domestic and foreign scientific conferences, Prof. Dr Duška Simova-Tošić has left behind a rich collection of insects and herbarium materials. During her lifetime, Prof. Simova deposited in and formally bequeathed to the Natural History Museum in Belgrade the collection “Diptera: Tipuloidea”, with a total of 146 species and 4143 specimens of Tipulidae, as well as a collection of herbaceous plants with Cecidomyiidae (“Herbarium cecidologicum Duška Simova”). The Limoniidae collection is kept at the Department of Entomology and Agricultural Zoology of the Institute of Phytomedicine at the Faculty of Agriculture, University of Belgrade. At the Faculty of Agriculture in Belgrade, Prof. Simova was an active member of many management boards and she was Head of the Department of Entomology and Director of the Institute for the Protection of Plants and Food Products (today called Phytomedicine). She was a member of the Yugoslav Entomological Society and the Plant Protection Society of Serbia, and a very active member of the Entomological Society of Serbia, which awarded her with a special certificate of thanks as a meritorious member in 2008. She was a member of the editorial board of the journal “Acta entomologica Serbica”. Prof. Simova was serious, hardworking, systematic, strict, authoritative, committed to her scientific and pedagogical work, recognized and respected by her colleagues and students, and, above all, modest. Despite all her obligations and engagements, Prof. Simova found the time to return to her hometown of Skopje, where she loved going as often as she could. We who knew Prof. Simova remember working together and socializing, as well as her curiosity and zeal until the last day of her life. All that she gave to science remains as a permanent and valuable legacy for future generations of entomologists.